Analisis Jumlah Koperasi Aktif dan Persentase Koperasi Sehat terhadap Volume Usaha Koperasi Kota Padang Panjang - Eliza, Eliza (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2019)
This study aims to examine the effect of the number of active cooperatives and the percentage of healthy cooperatives on the volume of cooperative businesses. The results obtained, that the coefficient of determination is 93.3%. While together (simultaneous) also has a positive and significant effect, which is 0.034 compared to alpha 0.05 for both independent variables. Likewise the case separately (partial), which has a positive and significant influence, namely the number of active cooperatives to the cooperative business volume of 0.584 when compared with alpha 0.05 indicating a greater value. Meanwhile, the percentage of healthy cooperatives has a value that is smaller than alpha 0.05, which is 0.045.